2019
DOI: 10.1051/e3sconf/201913501035
|View full text |Cite
|
Sign up to set email alerts
|

Reduction of greenhouse gas emissions from renewable energy technologies in agricultural sectors of Uzbekistan

Abstract: This paper presents the results of calculations to reduce greenhouse gas emissions in agricultural sectors of the Republic of Uzbekistan within the framework of the project: “Sustainable Agriculture Development and Climate Change Mitigation”. The initial data were the characteristics of the implemented installations based on renewable energy sources for the period of 2014-2018. Most of these installations were biogas settings based on the principle of anaerobic fermentation, as well as solar water heating and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(7 citation statements)
references
References 3 publications
0
6
0
1
Order By: Relevance
“…the expression is called the differential equation of rotation of a rigid body around a fixed axis. In equation (17), the moment of inertia Bz is an analogue of the mass m determined from the formula (6), is the effect F acts as the main vector of forces. Usually the turbine is affected by several forces determined by the formula (11), so…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…the expression is called the differential equation of rotation of a rigid body around a fixed axis. In equation (17), the moment of inertia Bz is an analogue of the mass m determined from the formula (6), is the effect F acts as the main vector of forces. Usually the turbine is affected by several forces determined by the formula (11), so…”
Section: Resultsmentioning
confidence: 99%
“…On the other hand, due to their self-sufficiency and low energy prices, solar energy applications in agriculture are expanding for irrigation, lighting, heating, cooling, and drying, which eventually lowers production costs and saves a sizeable amount of investment [15,16]. Solar energy is also getting more cost-effective and efficient, which effectively lowers global warming and makes it a practical answer for climate change issues [17][18][19][20][21]. The inverters are also contained in soundproof casing, and the solar 1142 (2023) 012029 IOP Publishing doi:10.1088/1755-1315/1142/1/012029 2 module has no moving parts.…”
Section: Introductionmentioning
confidence: 99%
“…The maximum disarrangement was 14 %, which is within the experimental inaccuracy. The elaboration of experimental data to identify the dependence of the height of the three-phase fluidized bed on the air velocity revealed that and is stated by the equation (3) The maximum discrepancy between the experimental and calculated data is . An equation was obtained for the dependence of the dynamic layer height on the rate and density of irrigation, which has the following form:…”
Section: Fig 2 the Effect Of Air Velocity In The Apparatus On The Hydraulic Resistance Of A Dry Grid Without A Nozzlementioning
confidence: 99%
“…In the Republic of Uzbekistan, one of the main areas of the economy is currently receiving a lot of attention: the development of technological equipment for the energy industry that meets modern standards, such as the modernization of cooling systems for circulating water and air conditioning [1,2]. The 2017-2021 Strategy of Actions for the Further Development of the Republic of Uzbekistan emphasized the necessity of reducing the economy's energy and resource intensity through widespread use of energy-saving technologies [3][4][5][6]. To some extent, this research aids in the completion of the regulations' tasks.…”
Section: Introductionmentioning
confidence: 99%
“…Diminishing the effects of climate change and minimizing CO 2 emissions by using alternative energy have positive impacts on the health of humans and have benefits for the surrounding ecosystem. As a result, shifting from fossil fuel consumption to renewable energy increases life expectancy and decreases the expenditure on the treatment of diseases (Anarbaev et al , 2019). On the other, various studies have investigated that health expenditure can promote health indices, such as life expectancy.…”
Section: Introductionmentioning
confidence: 99%